Akurasi Arah Kiblat Masjid-Masjid di Kabupaten Banjar - Rahman Helmi, S.Ag., MSI; H. Badrian, M.Ag. (Sharia Journal and Education Center Publishing, 2024)
Abstract Currently, the Qibla direction of mosques in Banjar Regency is still found to be inaccurate so that the prayer safes must be deviated from the direction of the building. However, a representative study to determine the accuracy of the Qibla direction of these mosques has not been conducted. To get a more comprehensive picture of the accuracy of Qibla direction and to find out the factors that cause the deviation of Qibla direction of mosques in Banjar Regency, it is necessary to conduct research. The measurement of Qibla direction was carried out by calculating the phalactic science using the Viincenty method. The finding of this research is that the accuracy of Qibla direction of mosques in Banjar Regency shows varying levels of accuracy. For the 40 mosques that have been studied, 5 mosques (13%) are highly accurate, 7 mosques (18%) are accurate and 28 mosques (70%) are inaccurate. The factors causing the variation in the accuracy of Qibla direction are the use of a non-standard compass, the use of a compass that has not followed the correct procedure, and the determination of Qibla direction based on the istiwa stick. Keywords: Qibla direction, accuracy, deviation, theodolite Keywords: Islamic Religious Education and Information Technology Abstrak Saat ini masih ditemukan arah kiblat masjid-masjid di Kabupaten Banjar yang kurang akurat sehingga saf salat harus diserongkan dari arah bangunan. Walaupun demikian, penelitian yang refresentatif untuk mengetahui akurasi arah kiblat masjid-masjid tersebut belum dilakukan. Untuk mendapatkan gambaran yang lebih komprehensif mengenai akurasi arah kiblat dan untuk mengetahui faktor-faktor penyebab deviasi arah kiblat masjid-masjid di Kabupaten Banjar dipandang perlu untuk dilakukan penelitian. Pengukuran arah kiblat dilakukan dengan penghitungan ilmu falak menggunakan metode Viincenty. Temuan penelitian ini adalah akurasi arah kiblat masjid-masjid di Kabupaten Banjar menunjukkan tingkat akurasi yang bervariasi. Untuk 40 masjid yang sudah diteliti, 5 masjid (13%) kategori sangat akurat, 7 masjid (18%) kategori akurat dan 28 masjid (70%) masih kurang akurat. Faktor-faktor penyebab bervariasinya keakuratan arah kiblat adalah penggunaan kompas yang tidak standar, penggunaan kompas yang belum mengikuti prosedur yang benar, dan penentuan arah kiblat berdasarkan tongkat istiwa. Kata Kunci: arah kiblat, akurasi, deviasi, theodolit